Investigative uses of overmodulation techniques in modular multilevel cascaded converter - Jayesh A. Gangurde; Rakesh Shriwastava; Deepak P. Kadam; Sunil Somnath Kadlag; Haridarshan S. Sonawane; Mohan P. Thakre (Bulletin of Electrical Engineering and Informatics, 2022)
Sinusoidal pulse width modulation (SPWM) is a method to generate the switching gate pulse of the converter. Overmodulation is a method where the modulation index exceeds the unity value and the system goes into the nonlinear region. To maintain the system in a linear region when operating in the overmodulation region, some techniques are developed. These techniques helped to operate the system in the linear range. Medium and high-power energy conversion systems mostly use a modular multilevel cascaded converter (MMCC), which has been an issue improving significantly in recent years. In this article, MMCC-based overmodulation techniques are compared with conventional PWM and analyzed on DC bus utilization (DBU), and total harmonic distortion (THD). MATLAB/Simulink digital platform used demonstrate overmodulation technique.